A New Anatomical Approach to Male Pectoral Volumization - Emmanuel Armando Flores González, MD; Ricardo Babaitis, MD; Raul Martin Manzaneda Cipriani, MD; Mauricio Schneider Viaro, MD; Hector Cesar Duran Vega, MD; Daniel Lobo Botelho, MD; Oliver René Ramírez Guerrero, MD; Noe Isaias Gracida Mancilla, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. In this article, we discuss a new technique of pectoralis major muscle volumization using ultrasound-guided fat grafting, considering a new surgical criterion that allows for larger volumes. Methods:. We present a retrospective observational descriptive study, which included men who underwent body contouring surgery during 2022–2023. As part of the study, measurements were taken before, immediately after, and at 3 months after surgery. Data were stored in a database and analyzed using SPSS statistical software, v23.0. Results:. The average age was 34.8 years [±8.2] and when evaluating the cases based on their body mass index, we found an average body mass index of 28.2 kg/m2 [±1.9]. When evaluating the paired differences between initial depth of pectoralis major–transoperative depth of pectoralis major, transoperative depth of pectoralis major–postoperative depth of pectoralis major at 3 months, and initial depth of pectoralis major–postoperative depth of pectoralis major at 3 months using the Student t statistic for related samples, statistically significant differences were obtained (P = 0.001). This is a preliminary short-term study revealing a new approach to volumizing the pectoralis major muscle and requires long-term follow-up. Conclusions:. The technique allows for an increase in muscle thickness. Measurements were taken immediately after infiltration and at 3 months, observing the presence of the fat graft and the increase in volume. In the future, it is important to perform long-term follow-up. No adverse events occurred during the study.